Comparative Study Between Holmium: Yag Laser and Pneumatic Lithotripsy in the Management of Upper Ureteric Stone (Bangladesh Journal of Urology, 2020)
Background:Among various intracorporeal lithotripters, Pneumatic lithotriptorhas become the widely used tool for the treatment of ureteric stones. Recently the Holmium:YAG laser has been used with a wide range of potential urological applications, including intracorporeal lithotripsy of ureteric stones.Objective: To compare the treatment of upper ureteric stone between laser and pneumatic lithotripsy.Materials and methods: One hundred patients with upper ureteric stone who underwent ureteroscopic lithotripsy in the Department of Urology, CMH, Dhakafrom October 2012 to September 2015 were enrolled in this study. Patients were divided into two groups. Group A (LL) were treated with holmium: YAG laser and Group B (PL) were treated with pneumatic lithotripsy. Two procedures were compared in term of stone fragmentation, stone clearance rate, duration of lithotripsy, complications and duration of post operativehospital stay. Patients were monitored as outpatients after one month and after three months with a kidney ureter and bladder radiograph and ultrasonograph. Patients with migrated fragments or incomplete clearance underwent an auxiliary procedure such as Extra Corporeal shock wave lithotripsy (ESWL).Results: Mean stone size was 1.36 ± 0.36 cm in group A (LL) and 1.37± 0.36 cm in group B (PL). The immediate stone clearance rate was significantly higher inGroup A (94.0%) than Group B (76.0%). Fragments proximal migration were 6.0% in LL group and 24.0% in PL group. Use of stone retrieval equipments (baskets, forceps) was 16.0% and 64.0% in LL and PL group respectively (p